Indução docente na educação infantil a partir de teses e dissertações no período de 2015 a 2019 - Lima, Danuza Roberta Pereira (2020)
The first years of the teaching career are essential for the constitution of professional identity, proving to be decisive in the establishment of professional practice throughout the career. The initial years of teaching are characterized as a period of intense learning and decision about staying in the profession. This period is also marked by situations that will influence the type of teacher that the beginner will become. Therefore, it is important for the beginning teacher to experience a process of accompaniment and teacher training during this period of his career, in the perspective of inducing teaching. In view of the above, this study aims to investigate the processes of teaching induction in early childhood education based on existing theses and dissertations in the theses and dissertations portal of the Coordination for the Improvement of Higher Education Personnel - CAPES in the period from 2015 to 2019. The study on screen has a qualitative approach and was carried out from a systematic review that consists of the analysis and systematization of the results of the studies found. Nine works defended between the years 2015 to 2019 on the CAPES thesis and dissertations portal were analyzed. The survey carried out showed that the theme of teacher induction is still scarce in Brazilian literature, especially of teachers in early childhood education, revealing itself as a recent research topic. It revealed that there is an urgent need to structure processes aimed at monitoring and training teachers and teachers beginning in early childhood education, considering the challenges inherent in the initial phase of the teaching career and the complexity of work in the first stage of basic education. It evidenced the scarcity of policies and programs that favor times and spaces in institutions destined to the individual and collective reflection of teachers and other education professionals, in addition to policies of teacher induction. What has been developed are specific actions aimed at training these professionals, but without continuity. It revealed the need to bring the university and schools of basic education closer together, in the direction of the intertwining of the two institutions so that they can create a new formative space in which all knowledge and the knowledge of all are considered and respected. As a possibility to overcome the challenges of the induction processes, the use of the teaching case as an important training strategy that can compose the policies and practices of teaching induction in view of its potential for the promotion of processes is suggested in this study for reflection and analysis about pedagogical practice in early childhood education.